Improved Efficiency of Flexible Organic Light-Emitting Diodes by Insertion of Ultrathin SiO2 Buffer Layers. (12th November 2013) - Huang, Chien-Jung; Chen, Kan-Lin; Sze, Po-Wen; Chen, Wen-Ray; Meen, Teen-Hang; Wu, Shi-Lun
Abstract : An ultrathin hole-injection buffer layer (HBL) using silicon dioxide (SiO2 ) by electron beam evaporation in flexible organic light-emitting diode (FOLED) has been fabricated. While the current of the device at constant driving voltage decreases as increasing SiO2 thickness. Compared to the different thicknesses of the buffer layer, the FOLED with the buffer layer of 4 nm showed the highest luminous efficiency. The atomic force microscopy (AFM) investigation of indium tin oxide (ITO)/SiO2 topography reveals changes at the interface between SiO2 and N, N′-bis-(1-naphthl)-diphenyl-1, 1′-bipheny-4, 4′-diamine (NPB), resulting in ultrathin SiO2 layers being a clear advantage for a FOLED. However, the SiO2 can be expected to be a good buffer layer material and thus enhance the emission performance of the FOLED.